Tips and Tricks for Answering the TOEFL Test in Listening Skills for Students of SMA Negeri 1 Pematangsiantar - Pangaribuan, Yemima Br; Sitorus, Ester; Sinambela, Chintya; Pangaribuan, Silvia S.; Herman, Herman (Universitas Ibn Khaldun, 2025)
This community service program (PkM) was conducted on May 3, 2025, at SMA Negeri 1 Pematangsiantar. The activity targeted Grade 11 students in the science program (IPA 1). The main goal was to introduce the students to the concept of TOEFL, explain its importance, and especially focus on the Listening Section. Many students in high schools are still unfamiliar with TOEFL, even though this test is important for those who want to study abroad or apply for scholarships. We designed this program as a three-hour session with a focus on listening skills. We did not use pre-tests or post-tests, but instead we gave one test at the end to check the students' understanding. The activity had three parts: first, a presentation about what TOEFL is, why it is important, and what the Listening Section looks like. Second, we explaithe ned strategies and tips to answer listening questions correctly. Third, we played audio recordings, discussed the questions with the students, and gave them practical advice on how to answer the questions. The result of this activity was very positive. The students became more aware of TOEFL and felt more confident about facing the Listening Section. Even though the activity was only for one day, the students actively participated and understood the basic techniques for listening comprehension. In conclusion, this program was effective in helping students understand and practice TOEFL listening strategies.